The efect of particle-size distribution on the flotation of two South African coals - G. Panopoulos; R. P. King; A. H. Juckes (The Southern African Institute of Mining and Metallurgy, 1986)
The flotation characteristics of two South African coals were investigated: one from the Dumacol Colliery in Natal, and the other from Landau Colliery in the WitbankCoal Field. Samples of fine coal (smaller than 1 mm)were studied, the Dumacol coal showing significantly better ash-liberation characteristics than the Landau coal. Neither coal was found to produce satisfactory flotation concentrates, except at very fine sizes. The poor flotation performance can be ascribed to the non-selective flotation of unliberated particles that may contain considerable quantities of ash. Flotation recoveries were greatest for particles between 100 and 200 µ m, and fell of rapidly as the size increased above 200 µ m. Very fine particles were found to float adequately, and acceptable concentrates can be made at comparatively high yields from materials smaller than 75 µ m. The flotation of ultrafine coal was demonstrated successfully in a continuous pilot plant. This result opens the way to a potentially viable industrial process for the beneficiation of ultrafines from the Witbank No. 2 seam, which for decades has been regarded as non-floatable.